Pelatihan Pembuatan dan Pemanfaatan Eco Enzyme dari Sampah Organik Rumah Tangga Pada Warga Binawidya - Benriwati Maharmi; Neri Puspita Sari; Yulia Setiani; Silfia Rini; Zaiyar Zaiyar (Asosiasi Dosen Pengabdian kepada Masyarakat Indonesia, 2022)
Garbage is a household product, which is produced every day. The household garbage becomes a big problem, if it can not be handled properly. Residents of RT 04 RW 09 Binawidya, Tampan district, city of Pekanbaru have experienced problems with waste such as unpleasant odors due to the accumulation of house yard waste before being disposed to a final disposal site. To reduce this problem, there are many solutions that can be done. One of them is to utilize organic waste from household, which is processed into Eco-Enzyme. The eco-enzymes made from household waste such as vegetable residues and fruit peels. It can produce environmentally friendly products such as floor cleaners, plant fertilizers, water purifiers and others. The eco-enzyme is very easy to make. The ingredients are used organic waste (vegetables and fruit peels), sugar and water in a ratio of 3:1:10. This paper explained the eco-enzyme production training that was given to housewives, aiming to use the waste produced by their households into useful products.